Adherence to Sports Nutrition Guidelines by Tennis Athletes Team Representing the University of Limpopo; Limpopo Province, South Africa - Thabiso, Sepudumo; Tshabaku, Sekgobela Tumelo; Juanita, Mamaila; Sylven, Masoga; Wisdom, Mboweni Ntsako (Journal Coaching Education Sports, 2023)
Tennis sport is gaining popularity among students at the University of Limpopo. However, compliance with sports nutrition guidelines by these athletes remains unknown. To evaluate the adherence of tennis athletes to sports nutrition guidelines. A purposive sampling technique was used to recruit 30 affiliated tennis athletes representing the University team. Ethical approval was obtained from TREC while consent was signed in written form by the athletes. Nutrients intake was collected using a 24-hour-recall questionnaire on three different days, validated with FFQ. Weight and height were collected to calculate nutritional requirements. Dietary data were analysed using SAMRC FoodFinder (v3) and averages were exported into the SPSS (v28). Descriptive statistics were used to establish compliance. Males predominate (53%) over females. Athletes were aged 20.3(±1.1) yrs. Half of athletes (50%) participated in tennis sport for ≤ 1 year. Most athletes attended tennis 3 – 6 times a week, once a day, for 2 – 3 hours. Most athletes relied on social media for nutrition information. The BMI was optimal (21.8±2.8 kg/m2 versus 21.1±1.8 kg/m2 for females and males respectively). Males consumed energy of 27±9.0 kcal/kg/day compared to females (24±8.0 kcal/kg/day). CHO (3.2 g/kg/day females and 3.6 g/kg/day males) and protein (0.7 g/kg/day females and 1.0 g/kg/day males) intakes were also consumed. Fat consumption was optimal for both females (0.6 g/kg/day) and males (0.7 g/kg/day). The dietary practices of the tennis athletes at the University of Limpopo are not in compliance with the sports nutrition guidelines.